PENENTUAN HARGA POKOK BERAS DI KECAMATAN KOTAMOBAGU TIMUR KOTA KOTAMOBAGU - Juliana R. Mandei; Theodora Katiandagho; Charles R. Ngangi; Jilly N. Iskandar (AGRI-SOSIOEKONOMI, 2011)
The research with the title "Determination of Floor Price of Rice in the Eastern District Kotamobagu,Kotamobagu City" was designed to determine the base price of rice in the district east of the city KotamobaguKotamobagu, and compare the prices of goods sold at market prices and government purchase price(HPP). This research was conducted from November to December 2010. Data obtained from primary andsecondary data. Primary data obtained from direct interviews using a questionnaire to farmers, and primarydata obtained from the relevant agencies. Determining the location of intentional (purposive sampling)where a small village and village Kobo Moyag chosen because it is the biggest rice producing region inthe Eastern District Kotamobagu. The samples were farmers conducted by simple random sampling.Analysis of the data used is the method of Full Costing by summing the total component cost.The results showed that the size of the average floor price in District of East Kotamobagu isRp4961.56 per kilogram. The average floor price of rice in Sub Moyag higher than Kobo Small Village.